Supervision of Academic Supervisor and Quality of ‎Education in Madrasah Ibtidaiyah - Nur Hasanah (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2019)
Supervisors are one of the most important elements in ensuring the quality of madrasah education. Therefore, the duty of the supervisor have to be in accordance with the work program about the quality of education in the madrasah is in accordance with the standards set by the madrasah. The maximum implementation of supervisory to the academic supervision will help the quality of madrasah education to be achieved. This study aims to determine the academic supervisory competence of madrasah supervisors, the quality of madarasah education, and the relation of academic supervisory competence and the quality of Madrasah Ibtidaiyah education in the Sub-district of West Ungaran Barat, Semarang District.This study used the method of observation, interviews, and documentation. And the data analysis used flow flows. The conclusion of this study was that the academic supervision competence of the Madrasah Ibtidaiyah supervisor has been carried out but has not been maximally in accordance with the supervisor's work program. While, the education quality of MI Nyatnyono 2 and MI Lerep in the process standards and results have not been maximized. And the relations of the supervisors' academic competency supervision and MI (Madrasah Ibtidaiyah) quality education are associative relations in the form of cooperation, accommodation and supervisory associations in conducting academic supervision in the MI so that the quality of MI education in standard processes and results can be carried out even though it is not maximized.